Left Ventricular Adaptation to 12 Weeks of Indoor Cycling at the Gym in Untrained Females - Hedman, Kristofer; Bjarnegård, Niclas; Länne, Toste (International Journal of Sports Medicine, 2017)
Cross-sectional studies provide evidence of larger cardiac dimensions and mass in endurance trained than in untrained females. Much less is known regarding adaptations in cardiac function following training in untrained subjects. We aimed to study left ventricular (LV) adaptation to indoor cycling in previously untrained females, in regard of LV dimensions, mass and function. 42 sedentary females were divided into 2 equally sized groups, either training indoor cycling at regular classes at a local gym for 12 weeks, in average 2.6 times per week, or maintaining their sedentary lifestyle. Echocardiography at rest and a maximal exercise test were performed before and after the intervention. Exercise capacity increased in average 16% in the exercise group (p<0.001), together with decreased heart rate at rest (p<0.05) and at 120 watts steady-state (p<0.001). There were no difference in systolic or diastolic function following the intervention and minimal increases in LV internal diameter in diastole (+1 mm, p<0.01). LV mass was unchanged with training (137±25 vs. 137±28 g, p=0.911). Our findings indicate that attending indoor cycling classes at a gym 2-to-3 times per week for 12 weeks is enough to improve exercise capacity, while a higher volume of training is required to elicit cardiac adaptations.
Keywords: endurance exercise training; echocardiography; athlete’s heart; exercise testing